P–754 A novel warmed device protecting the embryo transfer catheter is effective in preventing the cooling of embryos during the embryo transfer procedure. (6th August 2021) - Macklon, N; Larreategui, Z; Ferrando, M; Marti. Salat, M; Chiriu, A; Coat, C; Pere. Cano, I; Svalander, P
Abstract: Study question: Can cooling of embryos during the embryo transfer be alleviated with the use of a 37 °C temperature protective device covering the ET catheter? Summary answer: Cooling of embryos during embryo transfer can be effectively alleviated by using a 37 °C pre-warmed temperature protective device covering the ET catheter. What is known already: An optimized physicochemical environment is crucial for maintenance of normal homeostasis, metabolism, and spindle stability to minimize stress on gametes and embryos. During preimplantation embryo development, epigenetic reprogramming occurs and environmental stress factors including temperature can disrupt this critical process and potentially damage embryos. IVF laboratories use heated stages, warming blocks and incubators to control and maintain temperature within set control limits. However, it has recently been shown that during the ET procedure, the temperature of fluid in the catheter tip drops significantly. To date no means of preventing this has been reported, or to our knowledge, implemented. Study design, size, duration: In this prospective controlled study, 100 simulated embryo transfer procedures were carried out at 5 European clinics. The catheters were loaded with medium according to clinic protocol. In 50, the transfer catheter was then transported to the clinician and handled according to standard practice, and in the other 50 the catheter was covered with the temperature protecting device after loading but otherwise handled identically. 10 control and 10 intervention procedures were performed at each clinic. Participants/materials, setting, methods: The temperature inside the ET catheter tip (Wallace Sure View) was measured with a calibrated thermocouple probe (diameter of 0.25 mm) placed at the location of an embryo and monitored during standard operating ET procedures (control group), and with the ET catheter-syringe set inserted into a temperature protective device (37 °C pre-warmed aluminium core, 15x90 mm) allowing retraction of the ET catheter tip immediately after embryo loading (study group). No embryos were employed in this study. Main results and the role of chance: During standard operating ET procedures (control group), a considerable variation was observed in the embryo loading temperature between clinics, ranging from 34 °C to 37 °C. A profound temperature drop down to 20.8 °C–25.6 °C was recorded within 20 seconds of loading the ET catheter and in all 5 clinics a very rapid decline in catheter tip temperature down to ambient temperature was observed regardless of environment, type of workstation, or standard operating ET procedures in use. In contrast, when the ET catheter-syringe set was placed into a 37 °C pre-warmed temperature protective device from the time of embryo loading until the end of the simulated ET procedure, the drop of temperature was minimal, effectively maintaining the temperature at the loading temperature of between 34 °C and 37 °C °C throughout the simulated ET procedure. The mean loss of temperature of 14.8 °C in the control group was reduced to just to 0.4 °C in the study group. The consistent and profound differences in catheter tip temperature between the control and device groups across repeated measurements at different sites indicate the findings to be robust. Limitations, reasons for caution: Numerous permutations of laboratory culture systems exist and the equipment, consumables and procedure for ET, including time, are highly variable and operator dependent. Therefore, the results and conclusions of this study may not be universally applicable. Furthermore, the impact of embryo cooling during ET on live birth rate remains uncertain. Wider implications of the findings: The ET procedure represents a 'weak link' in temperature control from the IVF laboratory to the patient until the embryo is safely deposited into its physiological environment, the uterine cavity. We demonstrate the effectiveness of a novel device for maintaining the temperature during ET, which could potentially improve embryo viability. Trial registration number: Not applicable